Resolving new memories: a critical look at the dentate gyrus, adult neurogenesis, and pattern separation - Aimone, James B. (2011)
Recently, investigation of new neurons in memory formation has focused on a specific function – pattern separation. However, it has been difficult to reconcile the form of separation tested in behavioral tasks with how it is conceptualized according to computational and electrophysiology perspectives. Here, we propose a memory resolution hypothesis that considers the unique information contributions of broadly tuned young neurons and highly specific mature neurons and describe how the fidelity of memories can relate to spatial and contextual discrimination.